Physiotherapy and rehabilitation students' opinions on anatomy education: A cross-sectional survey study - Turhan, Begümhan (University School of Physical Education in Wrocław, 2020)
Introduction. The study aim was to establish physiotherapy students' opinions about anatomy education, to explore attitudes towards studying anatomy, and thus to evaluate possibilities to improve anatomy education. Methods. Second-year physiotherapy students (98 females, 57 males) voluntarily participated in this study. Data were obtained by a questionnaire, which consisted of 35 questions. Results. The participants' mean age was 22 ± 1.77 years. The grade point average of females was higher than that of males (p = 0.001). Although the study duration per week and grade point average were moderately correlated in females (r = 0.397, p = 0.001), no correlation was determined in males. The statement 'Anatomy courses motivate me for my carrier' achieved the highest mean score (1.45 ± 0.8). The least mean score (0.21 ± 0.2) regarded the association between the given anatomy education and clinical practice. For 75.48% of the students, the endocrine system was the most interesting. The musculoskeletal system was learnt the best (69.03%). Video records and course notes given by the lecturer were the most beneficial studying materials for practical and theoretical anatomy lectures, respectively (p < 0.05). The textbook recommended by the lecturer turned out the least beneficial material for both practical (1.74 ± 0.82) and theoretical (1.17 ± 0.83) anatomy (p < 0.05). Conclusions. It is anticipated that interactive educators will be more helpful to teach the lessons. Moreover, it seems that anatomy education in physiotherapy and rehabilitation departments may need revisions to enhance students' motivation and improve academic learning. © 2020 University School of Physical Education in Wrocław.
Keywords: Anatomy curriculum; Anatomy education; Basic science; Physiotherapy education